Responding to radical populism: Chavismo in Venezuela. Issue 2 (23rd February 2016) - Hawkins, Kirk A.
Abstract : What are the effective ways of responding to populists, especially radical populists in government? The pessimistic answer provided by Chavismo is that little can be done; most of the negative impact of highly populist movements cannot be avoided in the short to medium term. The reasons lie not only in Venezuela's unique oil-based economy, but in the country's previous failures of democratic governance, a condition shared by many developing countries. Such failures make it likely that radical populists will receive broad popular support. This does not suggest that international actors cannot play a useful role in responding to populism. But the most viable democratic strategy is a long-term one emphasizing patient efforts by domestic opponents to reorganize themselves into programmatic, pluralist options for the future.